Linking Agricultural Development Policies and Performance on Nigeria’s Economic Growth - Ibrahim MUSA; Yahaya ISMAIL; Sule MAGAJI (Loka: Journal Of Environmental Sciences, 2024)
Purpose:This study links agricultural development policies and performance on Nigeria’s economic growth, utilizing a quasi-experimental research design and employing statistical techniques such as simple tables, percentages, correlation analyses, the Johansen Cointegration test, and the ARDL bound test.Methodology:Using 34 years of secondary data sourced from the National Bureau of Statistics and the Central Bank of Nigeria, the study finds that government spending, particularly capital expenditure, recurrent expenditure, and loans to farmers, has a positive and significant effect on agricultural output.Findings:Capital investment emerged as a critical driver of productivity, while recurrent expenditure showed an inconclusive impact, signaling the need for further investigation. The coefficient of determination (R² = 86.3%) underscores the robustness of the model in explaining variations in agricultural output.Implication:Based on these findings, the study recommends increased capital investment, improved access to agricultural loans, continuous evaluation of recurrent spending, policy stability, and enhanced research and data collection.